Análise dos conflitos entre pescadores artesanais de lagosta no município de Icapuí, Ceará - Rodrigues, Danielle Viana (2013)
This study aims to analyze the disputes between groups of fishermen of Icapui municipality on the east coast of Ceará who carries on traditionally lobster fishing for their subsistence. These conflicts have manifested themselves in the form of intimidation, assaults and violent clashes between local fishermen who compete for the same fishery resources and fishing bank, causing financial damage and even death among them. This research has the following objectives a historical trajectory of fishing in the city since the beginning of the conflict, identifying their causes, giving voice to the fishermen involved through their stories, besides describing and analyzing the main social actors in order to understand the socioeconomic issues, environmental and cultural factors that underlie these conflicts. Therefore, this study applied the Life History method, widely used in social sciences, and two methods often used in conflict analysis: Typology of Fishery Conflict and Analysis of Social Actors. The analysis of conflict proposed by this research used primary data collected through a set of techniques: bibliographic review; "snowball method"; informal, semi-structured and structured interviews; and focus group. The research did a total of 23 interviews, involving fishermen, representatives of public agencies, civil associations (residents) and reporters who had covered the conflict episodes in the city. A brief history of lobster fishing conflicts of Ceará and Icapui was done, since the fifties (early exploration of the crustacean in the city) until the present day, in order to identify the real causes of these conflicts and classify them according typology suggested in the literature. The results showed that the main social actors are the communities of Redonda and Barrinha (among seventeen existing in the municipality), IBAMA and the Port Authority (public agencies responsible for fishery law enforcement) and the Ministry of Fisheries and Aquaculture (responsible for licensing and records that legalize the fishing activity). The main causes of conflicts are related to the persistence of a fishermen group in using and multiplying the artifacts of predatory fishing. This behavior has provoked reaction from fishermen who support responsible fisheries and have adopted the strategy of law enforcement done by their own, resulting in seizing and burning boats. This situation is exacerbated by failures in the official inspection and absence of effective public policies for the fishery sector.